1998
DOI: 10.1007/bf03161538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil moisture regimes on growth and survival of black willow (Salix nigra) posts (cuttings)

Abstract: A study was conducted under greenhouse conditions to examine the effects of various soil moisture regimes on black willow (Salix nigra) posts (cuttings). Five treatments representing a range of soil moisture regimes, from continuous flooding to mild drought, were imposed separately. A well-watered, welldrained treatment served as the control. Leaf gas exchange (stomatal conductance and net photosynthesis), survival, and biomass production of posts were evaluated. The stomatal conductance and net photosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 14 publications
3
39
4
Order By: Relevance
“…The roots of the Salicaceae, which includes willows and poplars, are known to be tolerant of anaerobic conditions for long periods, although inter-specific differences in this tolerance are great (Karrenberg et al, 2002). While some studies have observed willows thriving in beaver ponds after 5 years of inundation (Amlin and Rood, 2001), others have documented reduced growth in inundated conditions (Jackson and Atwood, 1996;Pezeshki et al, 1998). Indeed, some authors have suggested that growth of flooded willow stops after two growing seasons and mortality increases (Knighton, 1981;Ohmann et al, 1990).…”
Section: Effects Of Beaver On Willow Regrowthmentioning
confidence: 99%
“…The roots of the Salicaceae, which includes willows and poplars, are known to be tolerant of anaerobic conditions for long periods, although inter-specific differences in this tolerance are great (Karrenberg et al, 2002). While some studies have observed willows thriving in beaver ponds after 5 years of inundation (Amlin and Rood, 2001), others have documented reduced growth in inundated conditions (Jackson and Atwood, 1996;Pezeshki et al, 1998). Indeed, some authors have suggested that growth of flooded willow stops after two growing seasons and mortality increases (Knighton, 1981;Ohmann et al, 1990).…”
Section: Effects Of Beaver On Willow Regrowthmentioning
confidence: 99%
“…nigra is a wetland plant with adaptations for survival in flooded conditions including the development of lenticels, adventitious roots and aerenchyma tissue that facilitates transport of oxygen from aboveground shoots to belowground roots (Seago et al 2005). However, oxygen is also leaked into the rhizosphere surrounding the roots which may help moderate the effects of toxic reduced ions (Godfrey and Wooten 1981;Pezeshki et al 1998;Amlin and Rood 2001;Cronk and Fennessy 2001;Pezeshki 2001).…”
Section: Introductionmentioning
confidence: 97%
“…In general, hydrology exerts strong effects on both soilatmosphere gas exchange and soil redox dynamics (Pezeshki 2001;Niedermeier and Robinson 2007), and consequently, leaf stomatal conductance, photosynthesis (Pezeshki et al 1998;Li et al 2004), and plant biomass production (Kennedy et al 2003;Li et al 2004;Garcia-Serrano et al 2007;Jung et al 2009). Therefore, a better understanding of the relationship between plant growth and hydrology can improve the effectiveness of wetlands management and restoration (Brock and Britton 1995).…”
Section: Introductionmentioning
confidence: 99%